The Chimera in Lorca´s "Chimera": a reception study. - Filímonos, Cristina (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
Chimera is one of the Federico García Lorca´s three brief dramatic Dialogues. Chimera, in classical mythology, is a hybrid monster, however, over time the word “chimera” acquires another, metaphorical meaning, that of the desire of the impossible, the illusion. The aim of this paper is to uncover how the play´s title is connected to its essence, as well as whether it refers to the mythological monster or the secondary, abstract meaning. Firstly, the monster´s characteristics that could be applied to the feminine element of the play are analysed, as well as the rest of the classical references featured throughout the dialogue. Then, the chimeras, in other words, the impossible, unreachable desires that distress the play´s entire family are examined. In that way, the chimeric figure´s and characteristics´ reception are studied in one of Lorca´s theatrical plays and what is intended to be established is a meaning of the word which includes both the mythological and the metaphorical sense.
Keywords: Lorca; symbolism; Greek mythology; Classical tradition; Chimera